ANALISIS KRITIS MAKNA KONOTASI DALAM LIRIK LAGU GALA BUNGA MATAHARI KARYA SAL PRIADI - Maria Winata, Yuli; Zoni Sulaiman; Zainah Asmaniah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Song lyrics, as part of poetic literature, often contain connotative meanings that are not explicitly conveyed. This study aims to analyze the connotative meanings contained in the lyrics of Sal Priadi's song "Gala Bunga Matahari" and to examine listeners' understanding of these meanings through comments on Sal Priadi's YouTube channel. This study used a descriptive qualitative method with a semantic approach. The research data consisted of words, phrases, and sentences containing connotative meanings in the song lyrics, as well as netizen comments as supporting data. Data collection techniques used listening, note-taking, and documentation. The results show that the lyrics of Gala Bunga Matahari are dominated by positive connotations that represent longing, hope, loyalty, and acceptance of the loss of a loved one. Furthermore, most listeners were able to accurately grasp the song's connotative meaning, although there were variations in literal and irrelevant understandings. This study confirms that Sal Priadi's song lyrics possess strong depth of meaning and are relevant as material for semantic studies and literary learning.